Markets structure and secular stagnation - Natasha Rovo (LUISS Guido Carli, Department of Economics and Finance, Arcelli Centre for Monetary and Financial Studies, 2017)
I investigate the relation between market structure and Secular Stagnation, from a theoretical and an empirical standpoint. By means of a 3-periods OLG model, I show that an increase in the share of profits triggers a decline in the natural interest rate and employment. I extend the model to 16 five-year periods and I introduce exogenous job destruction and a matching function. Under labor market frictions, the steady state features permanently lower equilibrium interest rate and lower employment, and the increase in market power has stronger e↵ects, hence suggesting that neglecting these frictions may likely bias the evaluation of the phenomena behind Secular Stagnation. In particular, firms post less vacancies, employment falls, wage bargaining implies permanently lower wages and, the number of discouraged workers increases. The model rationalizes the contemporaneous decline of the employment rate, the input shares, and the equilibrium interest rate. The estimation of a structural VAR with long-run restrictions confirms the above results.
Keywords: D42; E24; E31; E52; 330; market structure; labor market; natural interest rate; secular stagnation; hysteresis